Arginyl‐tRNA‐protein transferase 1 (ATE1) promotes melanoma cell growth and migration. Issue 11 (20th May 2022) - Lazar, Ikrame; Fabre, Bertrand; Feng, Yongmei; Khateb, Ali; Frit, Philippe; Kashina, Anna; Zhang, Tongwu; Avitan‐Hersh, Emily; Kim, Hyungsoo; Brown, Kevin; Topisirovic, Ivan; Ronai, Ze'ev A.
Abstract : Arginyl‐tRNA‐protein transferase 1 (ATE1) catalyses N‐terminal protein arginylation, a post‐translational modification implicated in cell migration, invasion and the cellular stress response. Herein, we report that ATE1 is overexpressed in NRAS‐mutant melanomas, while it is downregulated in BRAF‐mutant melanomas. ATE1 expression was higher in metastatic tumours, compared with primary tumours. Consistent with these findings, ATE1 depletion reduced melanoma cell viability, migration and colony formation. Reduced ATE1 expression also affected cell responses to mTOR and MEK inhibitors and to serum deprivation. Among putative ATE1 substrates is the tumour suppressor AXIN1, pointing to the possibility that ATE1 may fine‐tune AXIN1 function in melanoma. Our findings highlight an unexpected role for ATE1 in melanoma cell aggressiveness and suggest that ATE1 constitutes a potential new therapeutic target. Abstract : The present study investigates the role of arginyl‐tRNA‐protein transferase 1 (ATE1) in melanoma biology. Our findings highlight the regulation of melanoma cell survival and migration capabilities by ATE1, suggesting that this enzyme might constitute a potential new therapeutic target.